RECONSTRUCTION OF ISLAMIC EDUCATION PSYCHOLOGY IN UNDERSTANDING THE LEARNING AND DEVELOPMENT OF CHILDREN WITH SPECIAL NEEDS - Tammam Sholahudin; Mahasri Shobahiya (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
This study examines the reconstruction of Islamic educational psychology in understanding the learning and development of children with special needs. The background of this research lies in the dominance of Western psychological paradigms, particularly the medical model of disability, which often overlooks spiritual and holistic dimensions. The objective of this study is to identify research trends, thematic structures, and opportunities for integrating Islamic psychological concepts into inclusive education. Methodologically, this study employs a quantitative bibliometric approach using data from academic publications analyzed through VOSviewer, including network, overlay, and density visualizations. The results indicate that Islamic education remains the dominant foundational theme, while emerging topics such as inclusive education, parental involvement, self-efficacy, and learning disabilities reflect a shift toward more practical and psychological approaches. However, a gap persists between theoretical Islamic concepts and their implementation in inclusive practices. In conclusion, the field is evolving as an emerging domain but lacks conceptual integration. The study implies the need for developing applied models, strengthening international collaboration, and integrating Islamic values with modern educational and technological approaches.